PENGARUH JUMLAH PENDUDUK, IPM DAN UMKTERHADAP TINGKAT PENGANGGURAN TERBUKA KABUPATEN/KOTA DI PROVINSI JAWA BARAT - Hafiz Maulana (2022)
This research aims to determine the effect of population, human development index and the district/city minimum wage on the open unemployment rate of all districts/cities in West Java Province, and in this research, one control variable was added, namely GRDP. The sampling technique in this research used a saturated sampling technique in 27 regions during 2015-2020, so that a total sample of 162 data was obtained from the Central Bureau of Statistics (BPS). This research uses panel data analysis by combining time series and cross section data. The results of the partial study show that the UMK has a significant positive effect, the population and GRDP have a significant negative effect, while the HDI has no effect on TPT. The results of the study simultaneously show that the population, HDI, UMK and GRDP have an effect on TPT